Personal-Social Guidance based on Social Skills Profile of High School Students - Yalda Suvita; Supriatna, Mamat; Kustiawati, Tati (ILIN Institute Makassar, 2024)
Abstract. The research is motivated by the importance of the social skills of adolescents, especially high school students, in fulfilling developmental tasks. The aim of the research is to produce personal-social guidance based on the social skills profile of high school students. The research uses a quantitative approach with descriptive methods. The research design used was a cross-sectional survey. The research participants were 258 class XI students at SMA Angkasa Lanud Husein Sastranegara for the 2023/2024 academic year. The research findings show that personal-social guidance is based on the social skills profile of high school students which is generally in the medium category. The resulting personal-social guidance is suitable for use based on rational testing by guidance and counseling experts and practitioners. The research results can be used as a reference in implementing personal-social guidance services in developing social skills in high school. Abstrak. Penelitian dilatarbelakangi oleh pentingnya kecakapan sosial remaja khususnya siswa SMA dalam pemenuhan tugas perkembangan. Tujuan penelitian yaitu menghasilkan bimbingan pribadi-sosial berdasarkan profil kecakapan sosial siswa SMA. Penelitian menggunakan pendekatan kuantitatif dengan metode deskriptif. Desain penelitian yang digunakan adalah survey cross-sectional. Partisipan penelitian berjumlah 258 siswa kelas XI di SMA Angkasa Lanud Husein Sastranegara Tahun Ajaran 2023/2024. Hasil temuan penelitian menunjukkan bimbingan pribadi-sosial berdasarkan profil kecakapan sosial siswa SMA yang secara umum berada pada kategori sedang. Bimbingan pribadi-sosial yang dihasilkan telah layak untuk digunakan berdasarkan uji rasional ahli dan praktisi bimbingan dan konseling. Hasil penelitian dapat dijadikan sebagai acuan dalam pelaksanaan layanan bimbingan pribadi-sosial dalam mengembangkan kecakapan sosial di SMA.